Transcatheter Closure of Post-operative Residual Ventricular Septal Defect Using a Patent Ductus Arteriosus Closure Device in an Adult: a Case Report - Mulyadi M Djer; Nikmah S Idris; Idrus Alwi; Ika P Wijaya (Acta Medica Indonesiana, 2016)
Transcatheter closure of perimembranous and muscular ventricular septal defect (VSD) has been performed widely and it has more advantages compare to surgery. However, transcatheter closure of residual VSD post operation of complex congenital heart disease is still challenging because of the complexity of anatomy and concern about device stability, so the operator should meticulously choose the most appropriate technique and device. We would like to report a case of transcatheter closure of residual VSD post Rastelli operation in a patient with double outlet right ventricle (DORV), sub-aortic VSD, severe infundibulum pulmonary stenosis (PS) and single coronary artery. The patient had undergone operations for four times, but he still had intractable heart failure that did not response to medications. On the first attempt. we closed theVSD using a VSD occluder, unfortunately the device embolized into the descending aorta, but fortunately we was able to snare it out. Then we decided to close the VSD using a patent ductus arteriosus (PDA occluder). On transesophageal echocardiography (TEE) and angiography evaluation, the device position was stable. Post transcatheter VSD closure, the patient clinical condition improved significantly and he could finally be discharged after a long post-surgery hospitalization. Based on this experience we concluded that the transcatheter closure of residual VSD in complex CHD using PDA occluder could be an effective alternative treatment.